Meeting the New Anne Shirley: Matsumoto Yūko’s Intimate Translation of Anne of Green Gables - Uchiyama, Akiko (TTR, 2013)
Akage no An, the Japanese translation of L.M. Montgomery’s Anne of Green Gables (1908), has enjoyed continued popularity in Japan since the translation was first published in 1952. This paper examines one of the many translations that have been published since then, Matsumoto Yūko’s Akage no An, published in 1993. Unlike previous translations, which generally targeted child readers, Matsumoto translated the book for adult readers. The notable difference in Matsumoto’s translation is her detailed endnotes explaining literary allusions and cultural references. This paper examines how Matsumoto translated Anne of Green Gables, with a particular focus on her relationship with the text. This relationship is viewed through the lens of feminist literary criticism, which, Matsumoto explains, relates to her approach to translation. Her translation is also discussed through the idea of girls’ intimate reading. While Matsumoto describes her approach as aligned with feminist literary studies, this paper argues that the success of her translation is also underpinned by her practice of “girls’ intimate reading.” Feminist literary studies and girls’ intimate reading are shown to be interconnected in Matsumoto’s work.